2019
DOI: 10.1681/asn.2018080810
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident Macrophages Promote Renal Cystic Disease

Abstract: BackgroundMutations affecting cilia proteins have an established role in renal cyst formation. In mice, the rate of cystogenesis is influenced by the age at which cilia dysfunction occurs and whether the kidney has been injured. Disruption of cilia function before postnatal day 12–14 results in rapid cyst formation; however, cyst formation is slower when cilia dysfunction is induced after postnatal day 14. Rapid cyst formation can also be induced in conditional adult cilia mutant mice by introducing renal inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 46 publications
5
83
0
Order By: Relevance
“…However, the importance of infiltrating macrophages may be model specific because genetic deletion of CCR2, the Ccl2 ligand, did not affect cyst severity in the cpk mouse model (23). Of interest, our recent data also indicate that inhibition of resident macrophage proliferation and accumulation results in a significant reduction in cyst severity (11). Regardless of the source of macrophages, these cells are able to release inflammatory cytokines that promote cyst growth.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the importance of infiltrating macrophages may be model specific because genetic deletion of CCR2, the Ccl2 ligand, did not affect cyst severity in the cpk mouse model (23). Of interest, our recent data also indicate that inhibition of resident macrophage proliferation and accumulation results in a significant reduction in cyst severity (11). Regardless of the source of macrophages, these cells are able to release inflammatory cytokines that promote cyst growth.…”
Section: Introductionmentioning
confidence: 89%
“…A possible mechanism explaining the variability in phenotypic progression is the presence of "modifying factors" that can accelerate cyst growth in the presence of PKD mutations (3)(4)(5)(6). Renal injury is one example of a modifier that can accelerate cystogenesis (3,(6)(7)(8)(9)(10)(11). We have shown that unilateral nephrectomy (UNx) in adult conditional Pkd1 knockout mice leads to accelerated cyst growth (6,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While multiple intrinsic defects in tubular cells homeostasis are observed in ADPKD [34][35][36] , accumulating evidence demonstrates that interstitial inflammation also plays an important role in the disease [6][7][8]10,37,38 . Yet, the nature of the factors mediating communication between tubular and immune cells and their impact on disease expression are not well-characterized.…”
Section: Discussionmentioning
confidence: 99%
“…First, polycystin deficiency triggers monocyte migration to the kidney through the induction of CCL2 7,10 . Second, kidney injury has been shown to promote cyst progression by triggering CSF1 dependent resident macrophage proliferation 37 . In turn, infiltrating macrophages drive tubular cell proliferation, possibly by releasing arginine metabolites 8 .…”
Section: Discussionmentioning
confidence: 99%